Strategi Kebijakan Fiskal Dalam Menghadapi Resesi Ekonomi melalui Kebijakan Pajak - Agus Subagiyo; Khikmatul Islah; Ratih Kumala; Dwikora Harjo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
In the first quarter of 2020, the Gross Domestic Product (GDP) of several countries has clearly illustrated the impact of the Covid-19 outbreak which has affected the decline in economic activity around the world, US (0.3 percent), Germany (-2.3 percent), China (-6.8 percent) and Singapore (-2.2 percent). In response to the global economic downturn, several countries have issued various monetary easing policies and fiscal policy packages with progressive schemes with significant value. The government continues to be aware of current global economic developments and has responded through various domestic fiscal stimulus policies that are provided for health care, protection of vulnerable communities, incentives for affected sectors and strengthening financial stability. One of the focuses is related to tax policy in the midst of a pandemic as a measure to anticipate the threat of a recession. With descriptive qualitative methods through literature studies, tax policies during this pandemic are described. The role of this tax is one of the many alternatives in facing the threat of a recession during a pandemic